Improving Transparency and Accountability in Public-Private Partnerships : Disclosure Diagnostic Report - Ghana - World Bank (World Bank, Washington, DC, 2021)
A World Bank Public-Private Partnerships (PPP) team conducted a study in Ghana between September 2016 and March 2017, using the PPP Disclosure Diagnostic template recommended by the World Bank, Framework for Disclosure of Information in PPPs. This study has been consolidated in the form of a PPP Disclosure Diagnostic Report for Ghana. The Diagnostic Report examines the political, legal, and institutional environment for disclosure in PPPs. Based on a gap assessment exercise with key political, legal, institutional and process findings benchmarked against the World Bank Framework, the Diagnostic Report makes specific recommendations to improve disclosure, including a recommended customized framework for PPP disclosure in Ghana. This Diagnostic Report recommends a systematic structure for proactively disclosing information through a customized framework for disclosure in PPP in Ghana. The report suggests a holistic approach to disclosure through predefined standards, tools, and mechanisms, allowing for increased disclosure efficiency. The recommended design for Ghana follows the World Bank Framework. The design is hierarchical and includes a logical framework that moves from a high-level mandate to disclose toward the basic elements that need to be disclosed.